PSYCHOLOGICAL CHARACTERISTICS OF MODERN SCHOOL TEACHER AND STUDENT INTERACTIONS (Proceedings of International Conference on Educational Discoveries and Humanities, 2024)
In the contemporary development of socio-economic relations worldwide, the significance of informal means of influencing interpersonal relations within service collectives is notably increasing. Consequently, the study of leadership phenomena gains particular relevance across various spheres of civil society.